2015
DOI: 10.1891/0739-6686.33.185
|View full text |Cite
|
Sign up to set email alerts
|

State of the Science of Pediatric Traumatic Brain Injury: Biomarkers and Gene Association Studies

Abstract: Objectives Our objective is to review the most widely used biomarkers and gene studies reported in pediatric traumatic brain injury (TBI) literature, to describe their findings, and to discuss the discoveries and gaps that advance the understanding of brain injury and its associated outcomes. Ultimately, we aim to inform the science for future research priorities. Data sources We searched PubMed, MEDLINE, CINAHL, and the Cochrane Database of Systematic Reviews for published English language studies conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The arduous process of enrollment in all TBI studies and particularly in pediatric TBI becomes especially problematic in the context of molecular genomic research. Without recruitment of a sufficient number of participants into sample repositories (biobanks), studies may lack sufficient power to detect statistically significant relationships between biological markers and clinical outcomes, delaying advances in precision health (Reuter-Rice, Eads, Boyce, & Bennett, 2015). Moreover, recruitment of large numbers of cases into biobanks promotes generalizability of findings to the clinical population of interest as well as fuels ongoing discovery by supporting secondary analysis and data sharing.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The arduous process of enrollment in all TBI studies and particularly in pediatric TBI becomes especially problematic in the context of molecular genomic research. Without recruitment of a sufficient number of participants into sample repositories (biobanks), studies may lack sufficient power to detect statistically significant relationships between biological markers and clinical outcomes, delaying advances in precision health (Reuter-Rice, Eads, Boyce, & Bennett, 2015). Moreover, recruitment of large numbers of cases into biobanks promotes generalizability of findings to the clinical population of interest as well as fuels ongoing discovery by supporting secondary analysis and data sharing.…”
mentioning
confidence: 99%
“…Biobanks are important because evidence suggests that some biomarkers may predict recovery or reflect pathological processes that could be targeted therapeutically (Au & Clark, 2017). Unfortunately, existing data is largely limited to adult studies and the state of the science lags behind for pediatric TBI (Reuter-Rice et al, 2015). Indeed, two recent literature reviews found pediatric-specific evidence was grossly underrepresented with biomarkers in pediatric TBI cases being examined in only 16 of 131 (Reuter-Rice et al, 2015) and 16 of 7,150 (Daoud et al, 2014) publications.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although genetic studies in pediatric TBI are still in their infancy, there is evidence that genetic factors may exist, such as the potential role of the apolipoprotein E ( APOE ) gene in TBI outcome (Bennett, Reuter-Rice, & Laskowitz, 2016; Kurowski, Martin, & Wade, 2012; Reuter-Rice, Eads, Berndt, & Bennett, 2015). A more complete understanding of the relationship of CV to the mechanism by which APOE polymorphisms influence functional outcome in this setting may have therapeutic significance.…”
mentioning
confidence: 99%